2020
DOI: 10.1212/wnl.0000000000009288
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperthermic treatment decreases perihematomal hypodensity

Abstract: ObjectiveTo investigate the effect on perihematomal hypodensity and outcome of a decrease in body temperature in the first 24 hours in patients with intracerebral hemorrhage (ICH). MethodsIn this retrospective study on a prospectively registered database, among the 1,100 patients, 795 met all the inclusion criteria. Temperature variations in the first 24 hours and perihematomal hypodensity (PHHD) were recorded. Patients ≥37.5°C were treated with antihyperthermic drugs for at least 48 hours. The main objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
2
18
0
2
Order By: Relevance
“…In addition to imaging features, the patient's baseline neurological status (e.g., as measured by the National Institutes of Health Stroke Scale score, Glasgow Coma Scale score, and other indexes) is also significantly associated with PHE progression (10). Advanced age is an independent risk factor for PHE (10,61). However, Peng et al (21) indicated that younger patients are more likely to develop delayed PHE formation, which may be due to agerelated differences in brain atrophy.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to imaging features, the patient's baseline neurological status (e.g., as measured by the National Institutes of Health Stroke Scale score, Glasgow Coma Scale score, and other indexes) is also significantly associated with PHE progression (10). Advanced age is an independent risk factor for PHE (10,61). However, Peng et al (21) indicated that younger patients are more likely to develop delayed PHE formation, which may be due to agerelated differences in brain atrophy.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Several laboratory parameters that have been confirmed to affect hematoma expansion, such as hyperglycemia, a high MMP-9 level, and a high white blood cell count, may also be positively associated with PHE progression (10,61,76,77). Gusdon et al (78) found that the ratio of neutrophils to lymphocytes is effective in predicting PHE growth.…”
Section: Laboratory Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Allerdings konnten in der i-DEF-Studie (Deferoxamine mesylate in patients with intracerebral haemorrhage) keine positiven Effekte von Deferoxamin auf das klinische Outcome, noch auf das PHE nachgewiesen werden. Auch hier könnte das Konzept eines Bundled-treatment-Approaches -wie in der rekrutierenden INTERACT-3-Studie (NCT03209258) -den kombinierten Effekt von separaten, wenig wirksamen Einzelmaßnahmen wie der Normothermie auf das PHE nachweisen [22].…”
Section: Perihämorrhagisches öDemunclassified
“…Die Anwendung von antithrombotischen Medikamenten muss aufgrund der Gefahr einer intrakraniellen Nachblutung jedoch gut abgewogen werden, weshalb von den Leitlinien pneumatische Kompressionsstrümpfe zur Prophylaxe tiefer Beinvenenthrombosen empfohlen werden. Im klinischen Alltag wer-den jedoch aufgrund der leichteren Umsetzung niedermolekulare Heparine (NMH) verwendet, obwohl keine ausreichenden Daten zu deren Sicherheit vorliegen [22,23]. Eine große Observationsstudie konnte zeigen, dass intrakranielle Blutungskomplikationen lediglich bei < 2 % der Patienten auftreten und NMH daher bei ICB Patienten sicher erscheinen, insofern sie erst nach stabilem Verlaufs-CT und bei nachgewiesenem Gerinnungsausgleich verabreicht werden [24].…”
Section: Antithrombotisches Managementunclassified